Penjadwalan dan Pengendalian Bahan Baku Benang Grey pada PT. Panggung Jaya Indah - Saufik Luthfianto; Dian Saadah (Program Studi Teknik Industri Universitas Setia Budi, 2023)
PT Panggung Jaya Indah Pekalongan is a manufacturing company in Indonesia that produces woven sarongs. The company uses conventional raw material scheduling techniques to plan raw materials. Scheduling is used to plan and control the supply of raw materials at the lowest or minimum possible cost. This research was conducted to estimate demand until 2023 and used the help of LINGO software for aggregate scheduling. It then continued with designing the Master Production Schedule (MPS) and raw material scheduling. The development of Material Requirements Planning (MRP) was carried out by comparing the effects of some lot-sizing scoring systems, which is the process of calculating the optimum order size of a material based on netting requirements. Lot-sizing methods in this study include period order quantity (POQ), economic order quantity (EOQ), and least total cost (LTC). By using the lot-sizing method, the company can manage raw material inventory efficiently and effectively. The batch size model used is the one that presents the smallest cost per unit of inventory.